Enhancing affordance perception in pre-service physical education teachers: effects of content knowledge, motor experience and visual experience programs - van Maarseveen, Mariëtte; Leenhouts, Jonas; de Witte, Annemarie; Flux, Eline; van Doorn, Hemke; van der Kamp, John (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examined the effects of educational programs focused on content knowledge, motor experience, and visual experience on the perceptual skills of pre-service physical education (PE) teachers. Based on an ecological approach, perceptual skill in PE teachers refers to their ability to perceive teaching affordances, i.e., the possibilities for teaching actions within the environment.MethodsA total of 60 PE pre-service teachers (age M = 21.0, SD = 2.3, 32% female) participated in educational cricket programs designed to enhance teaching skills. Participants were divided into three experimental groups (content knowledge, motor experience, visual experience) and one control group. Pre- and post-tests involved watching cricket scenarios to assess affordance perception, with gaze behavior tracked through eye-tracking technology.ResultsIn the post-test, participants demonstrated faster intervention times, reduced uncertainty, and a broader, more differentiated perception of affordances. This highlights improved adaptability in teaching environments. Although group differences were modest, the visual experience groups showed a larger increase in affordances related to facilitating learning than other groups. Across all groups, participants implemented more selective, impactful interventions, and relied less on verbal guidance.DiscussionThese findings suggest that structured education fosters more confident, adaptive teaching styles, with small but meaningful effects depending on the type of educational content. However, the study's short duration and reliance on video-based assessments may have limited its ecological validity. This highlights the need for teacher education rooted in authentic, interactive settings. Overall, this study demonstrates the value of incorporating content knowledge, motor experience and visual experience into PE teacher education programs to enhance pre-service teachers’ perceptual skills and improve the quality of physical education teaching.